2018
DOI: 10.1016/j.joto.2017.12.002
|View full text |Cite|
|
Sign up to set email alerts
|

Video head impulse test (vHIT) in migraine dizziness

Abstract: Background and objectiveMigraine is an extremely prevalent primary headache disorder that frequently associates parallel symptoms such as dizziness, tinnitus and hearing loss. Our aim is to investigate differences in video head impulse (vHIT) results with patients suffering from vestibular migraine (VM) and healthy people, taking into consideration mean values of vestibule ocular reflex (VOR) gain, occurrence of the compensatory saccades latency and amplitude. According to the results, determine the usefulness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 21 publications
4
14
1
1
Order By: Relevance
“…The study of vestibular-oculomotor reflex with v-HIT in our series was normal in all subjects with MV, including those who developed fluctuation of hearing during followup. v-HIT applied to MV patients did not show a clinical importance as reported by ElSherif et al who compared healthy subjects and MV patients and found no alterations in gain or other parameters, underscoring the normality of vestibular-ocular reflex in MV patients 12 .…”
Section: Discussionsupporting
confidence: 50%
“…The study of vestibular-oculomotor reflex with v-HIT in our series was normal in all subjects with MV, including those who developed fluctuation of hearing during followup. v-HIT applied to MV patients did not show a clinical importance as reported by ElSherif et al who compared healthy subjects and MV patients and found no alterations in gain or other parameters, underscoring the normality of vestibular-ocular reflex in MV patients 12 .…”
Section: Discussionsupporting
confidence: 50%
“…VOR gain in the video head impulse tests was defined as the ratio of the area under the velocity curves of the right eye to that of the head ( 13 ). According to previous studies ( 14 , 15 ), normal VOR gain is specified by the video head impulse test (ICS Impulse®, GN Otometrics, Denmark) as >0.8 for the lateral canals and >0.7 for the vertical canals. Subjects who underwent surgical plugging were instructed to undergo serial video head impulse tests before surgery; immediately after surgery (within 1 week); and at 2, 6, and 12 months after surgery, if available.…”
Section: Methodsmentioning
confidence: 99%
“…They found that caloric test was abnormal in 22% of patients while the vHIT showed horizontal VOR deficit in 9% of patients. Also ElSherif et al, 22 reported that 26%of the vestibular migraine group exhibited abnormal vHIT results in the form of refixation saccades with normal VOR gain (18%), and low VOR gain with refixation saccades in (7.5%). They reportd that the presence of covert saccades despite normal VOR gain is a correction of eye drifts to the target position and it has been suggested that the presence of refixation saccades with normal VOR gain is part of the process of aging of the vestibular system.…”
Section: Discussionmentioning
confidence: 97%